Validity of CSF alpha-synuclein to predict psychosis in prodromal Alzheimer's disease - Monge-García, Sonia; García-Ayllón, María-Salud; Sánchez-Payá, José; Gasparini-Berenguer, Ruth; Cortés-Gómez, María-Ángeles; Sáez-Valero, Javier; Monge-Argilés, José-Antonio (Frontiers in Neurology, 2023)
Background: Alzheimer’s disease (AD) together with the psychotic symptoms (PS) involves a poor prognosis and may be associated with unbalances in key neural proteins such as alpha-synuclein (AS). Aim: The aim of the study was to evaluate the diagnostic validity of AS in the cerebrospinal fluid (CSF), to predict the emergence of PS in patients with prodromal AD. Material and methods: Patients with mild cognitive impairment were recruited between 2010 and 2018. Core AD biomarkers and AS were measured in CSF obtained in the prodromal phase of the illness. All of them that followed NIA-AA 2018 criteria for AD biomarkers, were treated with anticholinesterasic drugs. Current criteria for psychosis were applied during follow-up, and the requirement of neuroleptic drugs was necessary to consider the inclusion in the psychosis group. Several comparisons were made considering the time of emergence of PS. Results: A total of 130 prodromal AD were included in this study. Fifty of them (38.4%) accomplished the PS criteria within 8 years follow-up. AS was a valuable CSF biomarker to differentiate between psychotic and nonpsychotic groups, in every comparison made depending of the onset of PS. The level of AS 1257 pg/mL reached at least 80% of sensitivity. Conclusion: To our knowledge, this was the first time that a CSF biomarker showed diagnostic validity to predict PS in prodromal AD.